All planar compact size microstrip CRLH arbitrary coupling directional coupler. Issue 1 (20th November 2012) - Ibrahim, Amr A.; Safwat, Amr M. E.; El‐Hennawy, Hadia
Abstract A new compact size microstrip arbitrary coupling directional coupler (DC) based on the coupled line composite right/left handed (CL‐CRLH) unit cell is proposed. The coupler is patterned on a single metal layer, does not use vias, and occupies 45 × 11 mm2 area. Its bandwidth is 400 MHz centered around 2.4 GHz and it provides −3 dB coupling coefficient. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:115–119, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27270